Conformational variability of DNA double helix - Chesnokov, Yu. V. (Ovoshchi Rossii, 2020)
Deoxyribonucleic acid (DNA) is one of the main carriers of hereditary information. The structural physicochemical information of DNA ultimately determines the structure and functioning of all living organisms. In DNA, various mutational events accumulate and recombination events occur, which lead to the variability of organisms and are subject to both natural and artificial selection. The interaction "genotype-environment" inherent in all living organisms is also characteristic of DNA, which is located in the intracellular and intranuclear physicochemical environment of water molecules, sugars, metal ions, pH, nucleotides and other components. The establishment and study of the physicochemical properties of native DNA contributes to not only understanding the mechanisms of the structure of the main hereditary biomolecule, but also to clarify their functioning, as well as interaction with other molecules at the molecular level. The discovery of various forms of double helices: A, Aʹ, B, α-Bʹ, β-Bʹ, C, Cʹ, Cʹʹ, D, E and Z suggests the idea of molecular genetic diversity existing at the DNA level and the establishment of their structural and functional features can lead to an understanding of the implementation of genetic information at the general biological level. The structure of natural DNA as a whole, apparently, does not depend on the sequence and nucleotide composition. For natural molecules - satellite DNA with repeats or DNA without repeats, the presence of only A-, B- and C-forms has been confirmed. The structure of DNA depends not only on temperature, but also on the nature of the cations present. The presence of a certain amount of metal ions in the medium can lead to the transition of the B-form of DNA to the Zform. The B ↔ Z transition modifies the general structure of DNA and, therefore, may be important for the regulation of gene expression. The study of the biological role of Z-DNA, possibly in the near future, will help to understand the mechanism of gene expression, primarily of an epigenetic nature, which has not yet been fully elucidated.